Pengaruh Penerapan Sistem E-filing Terhadap Tingkat Kepatuhan Wajib Pajak Orang Pribadi Dalam Pelaporan SPT Tahunan Dengan Relawan Pajak Sebagai Variabel Moderasi Pada Tax Center UIN Sayyid Ali Rahmatullah Tulungagung - Fikri Presa Permadi; Ali Mauludi (Jurnal Akuntansi dan Pajak, 2023)
This study aims to determine the effect of implementing the e-filing system on the level of individual taxpayer compliance with tax volunteers as a moderating variable. This research uses associative quantitative method. Primary data collection from this study is by using a questionnaire distributed to taxpayers registered at the Tax Center as many as 100 respondents. The results of this study, namely the application of the e-Filing system has a positive and significant effect on the level of individual taxpayer compliance, which can be seen from the significant value (0.004) where the value is below (0.05). Thus when the implementation of the e-filing system is used properly, compliance will increase. Then, testing the moderating variable on the effect of implementing the e-filing system on the compliance level of individual taxpayers which indicates that the moderation effect provided is significant positive and capable of moderating, meaning that if the implementation of the e-filing system and tax volunteers increases by one unit, the level increase in taxpayer compliance.